2020
DOI: 10.1007/s00493-019-4009-0
|View full text |Cite
|
Sign up to set email alerts
|

Unbalancing Sets and An Almost Quadratic Lower Bound for Syntactically Multilinear Arithmetic Circuits

Abstract: We prove a lower bound of Ω(n 2 / log 2 n) on the size of any syntactically multilinear arithmetic circuit computing some explicit multilinear polynomial f (x 1 , . . . , x n ). Our approach expands and improves upon a result of Raz, Shpilka and Yehudayoff ([RSY08]), who proved a lower bound of Ω(n 4/3 / log 2 n) for the same polynomial. Our improvement follows from an asymptotically optimal lower bound for a generalized version of Galvin's problem in extremal set theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…D-AC p sD-AC p : there only is sD-AC p ≤ D-AC p to prove. Let C ∈ D-AC p , if g ∈ C is a +-node such that x ∈ var(g r ) and x ∈ var(g l ), then add a ×-node between g l and g whose successors are g l and Note that completing the map for positive AC might be very hard: in fact, it would in particular require showing strong lower bounds for D-AC p , a well-known open problem in complexity theory for which the best current result is a recent nearly quadratic lower bound (Alon, Kumar, and Volk 2020). Another question is the relations between the map of monotone AC and that of positive AC: when imposing determinism, the expressive power of positive AC is exactly that of monotone AC, while for unrestricted circuits it is known that positive AC are more succinct than monotone AC (Valiant 1980).…”
Section: Beginning the Map For Positive Acmentioning
confidence: 99%
“…D-AC p sD-AC p : there only is sD-AC p ≤ D-AC p to prove. Let C ∈ D-AC p , if g ∈ C is a +-node such that x ∈ var(g r ) and x ∈ var(g l ), then add a ×-node between g l and g whose successors are g l and Note that completing the map for positive AC might be very hard: in fact, it would in particular require showing strong lower bounds for D-AC p , a well-known open problem in complexity theory for which the best current result is a recent nearly quadratic lower bound (Alon, Kumar, and Volk 2020). Another question is the relations between the map of monotone AC and that of positive AC: when imposing determinism, the expressive power of positive AC is exactly that of monotone AC, while for unrestricted circuits it is known that positive AC are more succinct than monotone AC (Valiant 1980).…”
Section: Beginning the Map For Positive Acmentioning
confidence: 99%
“…My proof used a combination of Gröbner basis methods and linear algebra. Srinivasan gave a simpler proof which combined Fermat's little Theorem with linear algebra (see [5]). Alon found a third proof based on the Combinatorial Nullstellensatz (see [3]).…”
Section: Introductionmentioning
confidence: 99%
“…A seminal work of Raz [13] showed that multilinear formulas computing det n or perm n must have size n Ω(log n) . Although we know strong lower bounds for multilinear formulas, the best known lower bound against syntactic multilinear circuits is almost quadratic in the number of variables [1]. Note that any multilinear ABP of n O (1) size computing f on n variables can be converted to a multilinear formula of size n O(log n) computing f .…”
Section: Introductionmentioning
confidence: 99%
“…Although we know strong lower bounds for multilinear formulas, the best known lower bound against syntactic multilinear circuits is almost quadratic in the number of variables [1]. Note that any multilinear ABP of n O (1) size computing f on n variables can be converted to a multilinear formula of size n O(log n) computing f . In order to prove super-polynomial lower bounds for ABPs, it is enough to obtain a multilinear formula computing f of size n o(log n) or prove a lower bound of n ω(log n) for multilinear formulas, both of which are not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation